Commendation for Tullio Seppilli - Margaret Lock (AM. Rivista della Società Italiana di Antropologia Medica, 2020)
I had the pleasure of meeting Tullio Seppilli several times, in both Rome and Montreal. The father of medical anthropology in Italy, he was a scholar of the first order, and established a politically engaged style of medical anthropology that is historically informed and inspired by the work of Antonio Gramsci.